The strategic differences between short- and long-term portfolio management in selecting debt and equity securities - Azis, Indrawan (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study evaluates the strategic differences between short- and long-term portfolio management in selecting debt and equity securities. It examines how these strategies impact portfolio performance, taking into account risk tolerance, time horizons, and external economic factors such as interest rates and inflation. The research employs a qualitative approach using a Systematic Literature Review (SLR) methodology. By synthesizing theoretical perspectives, particularly Modern Portfolio Theory (MPT), and integrating findings from recent studies, the research provides a comprehensive analysis of portfolio management strategies across varying investment horizons. The findings underscore the complementary roles of debt and equity in portfolio management. Debt securities are crucial for ensuring stability and capital preservation in short-term strategies, while equity securities, with their higher growth potential, are essential for long-term investment horizons. External factors, such as interest rate fluctuations and inflation, significantly influence asset allocation decisions. Diversification, across asset classes and geographically, emerges as a critical strategy for balancing risk and optimizing returns. The discussion highlights how aligning portfolio strategies with specific financial goals and market dynamics can enhance performance. This study provides theoretical and practical insights for investors and financial practitioners. It offers actionable guidance for optimizing portfolio strategies, emphasizing the importance of adapting asset allocations to dynamic market conditions. Managerially, the findings inform the design of investment products tailored to client needs and financial objectives.